2016
DOI: 10.1021/jacs.6b05897
|View full text |Cite
|
Sign up to set email alerts
|

Self-Aggregating Deep Cavitand Acts as a Fluorescence Displacement Sensor for Lysine Methylation

Abstract: A dual-mode aggregative host:guest indicator displacement sensing system has been created for the detection of trimethylated peptides and determination of histone demethylase activity. The combination of selective recognition of suitably sized trimethylammonium salts and reversible lipophilic aggregation of the host:guest complex provides a unique quenching mechanism that is not only dependent on affinity for sensitivity but the lipophilicity of the indicator. In addition, aggregation can be controlled by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 32 publications
(39 reference statements)
0
78
0
Order By: Relevance
“…We have previously shown that the combination of cavitand 1 and a suitable fluorophore allows sensing of Kme 3 peptides via FDA. 15 This concept can be extended to allow site-selective Kme 3 recognition by the application of cavitands 1–3 in an array-based format, 16 followed by discrimination via principal component analysis (PCA). 17 The sensor can discriminate Kme 3 residues at different positions on peptides, and even sense remote changes in peptide structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the combination of cavitand 1 and a suitable fluorophore allows sensing of Kme 3 peptides via FDA. 15 This concept can be extended to allow site-selective Kme 3 recognition by the application of cavitands 1–3 in an array-based format, 16 followed by discrimination via principal component analysis (PCA). 17 The sensor can discriminate Kme 3 residues at different positions on peptides, and even sense remote changes in peptide structure.…”
mentioning
confidence: 99%
“…17 The sensor can discriminate Kme 3 residues at different positions on peptides, and even sense remote changes in peptide structure. The sensitivity of the system to methylation site 16 and state 15 suggests that it would be capable of site-selective monitoring of methylation enzyme activity (Figure 1). …”
mentioning
confidence: 99%
“…Evidently 13 also forms micelles, which incorporate the 2·4 complex, causing additional aggregation-based quenching of 4 . 26 While unexpected, this phenomenon provides another variable for discrimination of lipophilic guests, one that is not dependent on cavity-based recognition.…”
Section: Resultsmentioning
confidence: 97%
“…26 The binding of fluorescein guest 5 in host 1 causes aggregation of the lipid-like host (Fig. 1b) and concomitant aggregation-based quenching of the guest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation